2009
DOI: 10.1016/j.physbeh.2009.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Stressor controllability and Fos expression in stress regulatory regions in mice

Abstract: Controllability is an important determinant of the effects of stress on behavior. We trained mice with escapable (ES) and inescapable (IS) shock and examined behavioral freezing and Fos expression in brain regions involved in stress to determine whether stressor controllability produced differential activation of these regions. Mice (C57BL/6J) were trained to escape footshock by moving to a safe chamber in a shuttlebox. This terminated shock for both ES mice (n=5) and yoked-control mice receiving IS (n=5). Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 64 publications
3
30
0
Order By: Relevance
“…Thus, our finding of an NpHR-induced increase in neuronal activity in CNA relative to that observed in the control mice is consistent with the intra-amygdaloid connectivity. CNA neurons fire in response to footshock, 57 and some, 35,58 but not all, 30 studies have reported increased c-Fos in CNA in response to conditioned stimuli. Activation of CNA appears to induce the generation of fear behavior and physiological responses via descending brain stem projections, 59 for example, electrical stimulation of CNA can promote REM in some situations whereas its inhibition suppresses REM.…”
Section: Changes In C-fos Expression In Stress and Arousal Neurocircumentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, our finding of an NpHR-induced increase in neuronal activity in CNA relative to that observed in the control mice is consistent with the intra-amygdaloid connectivity. CNA neurons fire in response to footshock, 57 and some, 35,58 but not all, 30 studies have reported increased c-Fos in CNA in response to conditioned stimuli. Activation of CNA appears to induce the generation of fear behavior and physiological responses via descending brain stem projections, 59 for example, electrical stimulation of CNA can promote REM in some situations whereas its inhibition suppresses REM.…”
Section: Changes In C-fos Expression In Stress and Arousal Neurocircumentioning
confidence: 97%
“…29,30 Sections were labeled either with rabbit monoclonal anti-CaMKII (1:250, EP1829Y, Abcam, Cambridge, MA) or mouse monoclonal anti-GABA (1:2000, A0130, SigmaAldrich, St. Louis, MO) followed by the fluorescent secondary antibodies goat anti-rabbit Alexa Fluor 568 (1:200, Invitrogen) or goat anti-mouse Alexa Fluor 430 (1:200, Invitrogen), respectively. All blocking steps were done in PBS containing 3% normal goat serum (NGS, G9023, Sigma-Aldrich), 2% nonfat dry milk and 0.1% Triton X-100.…”
Section: Camkiiα and Gaba Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Such a pattern of Fos expression in the mouse brain is similar to that reported in rats exposed to WAS with Fos-immunoreactivity localized in the BNST, lateral septum, PVN, LC, dorsal raphe nucleus, VLM, NTS and lumbo-sacral spinal cord (Bonaz and Taché, 1994; Million et al, 2000). Other studies established that several stressors including restraint stress (O'Mahony et al, 2010), foot shock (Liu et al, 2009), hypertonic saline injection (Pirnik et al, 2004), ether (Korosi et al, 2005) or swim stress (Stone et al, 2007) induced Fos in stress-responsive neuronal populations in specific brain nuclei in mice namely the cingulate cortex, amygdala, PVN, Arc, paraventricular thalamic nucleus, Hi, EW, LC, dorsal raphe nucleus or VLM (Korosi et al, 2005; Liu et al, 2009; O'Mahony et al, 2010; Stone et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, studies investigating Fos expression as a marker of neuronal activity have consistently shown that a set of structures are activated in response to the exposure to different stressors in animal models of depression, which includes the mPFC, the hippocampus, the lateral septum, the nucleus accumbens, the amygdaloid nuclei (basolateral, central and medial), the PVN, the locus coeruleus, the thalamus (mainly the paraventricular), the PAG, and the raphe nuclei [MRN and DRN;(Bilang-Bleuel et al 2002;Bruijnzeel et al 1999;Duncan et al 1993;Duncan et al 1996;Liu et al 2009;Muigg et al 2007;Ons et al 2004;Roche et al 2007;Wulsin et al 2010)]. Neuroimaging and post-mortem studies with depressed individuals have also shown significant activity and morphological changes in many of these structures [for review see (Krass et al 2011;Price and Drevets 2010)].…”
Section: Discussionmentioning
confidence: 99%